Under The Shadow of Patriarchy: Women Position in Minangkabau Matrilineal System - Saputri, Rahmah Eka; Amril; Gusti, Erma; Nurjannah (AJIS: Academic Journal of Islamic Studies, 2024)
In traditional books it is often said that women in Minangkabau have a high position. The tradition that based on the syariah Islam is presumed to value her exixtance, care about her welfare, and listen to her opinion. This argument is often directed to the conclusion that the principle of gender equality has finally been implemented in the reality of Minangakabau society. However, in reality, such equality is not found in traditional meetings which are still patriarchal. This patriarchal pattern can also be seen in the philosophy of tali tigo sapilin (three twisted ropes) which symbolizes the three main leaders in Minangkabau society, namely niniak mamak, alim ulama, and cadiak pandai (tribal leader, religious leader, and scholar). The elimination of the Bundo Kanduang element in this philosophy seems to contradict the narrative of equality being promoted. Therefore, this article aims to examine in more depth the patriarchal patterns inherent in traditional books and in the reality of matrilineal Minangkabau society. The method used in this research is the critical analysis method. This research shows that Minangkabau women are, on the one hand, protected in terms of by their welfare by the customs. However, on the other hand, traditional reality shows that Minangkabau women are actually positioned as secondary creation, which is the main feature of patriarchal society.